Disparities in stage at diagnosis of head and neck tumours in Brazil: a comprehensive analysis of hospital-based cancer registriesResearch in context - Flávia Nascimento de Carvalho; Marianna de Camargo Cancela; Luciano Mesentier da Costa; Luís Felipe Leite Martins; Fernando Luiz Dias; Dyego Leandro Bezerra de Souza; Luis Felipe Ribeiro Pinto (The Lancet Regional Health. Americas)
Summary: Background: The advanced stage of cancer is a determining factor in poor prognosis. Head and neck squamous cell carcinomas (HNSCC) are highly incident in Brazil, but similarly to many Low and Middle-Income Countries, data is limited regarding the proportion of tumours diagnosed at advanced clinical stages and the main factors associated with it. Therefore, this study aimed to identify the factors associated with advanced stage of HNSCC in Brazil. Methods: Cross-sectional study based on secondary data collected from Hospital-based Cancer Registries (HBCR) between 2000 and 2017. Descriptive data analysis and Poisson regression with robust variance were performed to determine prevalence ratios (PRs). Findings: Among 145,365 HNSCC cases, 78.2% (90,267/115,371) were diagnosed at stages III or IV. The highest percentage of advanced-stage tumours were hypopharyngeal [91.3% (10,186/11,159)], followed by oropharyngeal [86.6% (28,578/32,991)], oral cavity [75.1% (27,121/36,120)], and laryngeal cancer [69.5% (24,382/35,101)]. We observed annual increase trends of 0.29% and 0.38% for oral cavity and oropharyngeal late-stage tumours, respectively. Patients younger than 50 years old, with a low education level, presenting a primary tumour located in the hypopharynx or oropharynx, and alcohol and tobacco consumers were positively associated with advanced stage. Furthermore, we observed a dose–response effect of a statistically significant reduction in the prevalence of cases diagnosed in advanced stages as the patients' age group or education level increased. Interpretation: Diagnosis of HNSCC at advanced clinical stages in Brazil was associated with age, primary tumour site, and socioeconomic factors that must be mitigated, allowing more universal and equitable access and diagnosis at earlier stages. Funding: No funding.